2023
DOI: 10.2147/clep.s442054
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Bile Acid Diarrhea in Denmark

Martin Kårhus,
Anne-Marie Ellegaard,
Matilde Winther-Jensen
et al.

Abstract: Objective Bile acid diarrhea (BAD) is a socially debilitating disease with frequent bowel movements, urgency, and fecal incontinence as the main symptoms. It is caused by excessive bile acid levels in the colon and is most commonly treated with bile acid sequestrants. It is estimated that 1–2% of the population suffers from the disease, but only a fraction of these are properly diagnosed with the gold standard ⁷⁵selenium-homotaurocholic acid (SeHCAT) test. Here, we use nationwide registries to des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…1 Our included number of cases reflects a prevalence about 0.1% in Denmark using the same case definition. 34 Some patients with undiagnosed BAD could have been included as controls of this study, but we deem the impact of such misclassification bias negligible. Increasing awareness of BAD means a higher number of diagnosed cases in recent years, so more data should be available for epidemiological studies of BAD in the near future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Our included number of cases reflects a prevalence about 0.1% in Denmark using the same case definition. 34 Some patients with undiagnosed BAD could have been included as controls of this study, but we deem the impact of such misclassification bias negligible. Increasing awareness of BAD means a higher number of diagnosed cases in recent years, so more data should be available for epidemiological studies of BAD in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing awareness of BAD means a higher number of diagnosed cases in recent years, so more data should be available for epidemiological studies of BAD in the near future. 34 We encourage researchers with access to similar data from other countries to investigate longterm outcomes of BAD.…”
Section: Discussionmentioning
confidence: 99%
“…The study provides a comprehensive analysis of the demographic characteristics of individuals suffering from bile acid diarrhea (BAD) in Denmark, based on national registries. 1 …”
Section: Dear Editormentioning
confidence: 99%
“…The study provides a comprehensive analysis of the demographic characteristics of individuals suffering from bile acid diarrhea (BAD) in Denmark, based on national registries. 1 The authors used a robust methodology, utilizing the Danish national registry to identify individuals with BAD, defined by a diagnosis of ICD10 code K90.8B or a SeHCAT test followed by a prescription of bile acid sequestrants within 365 days. The study revealed important findings, including regional differences in the frequency of BAD diagnoses in Denmark, lower income and education levels among individuals suffering from BAD compared to matched controls, and an increase in the number of BAD diagnoses over time.…”
mentioning
confidence: 99%
“…The results of this research have advantages, namely: 1) Identify individuals with bile acid diarrhea (BAD) in Denmark using data from the national registry, 2) Identify individuals suffering from BAD based on ICD10 diagnosis codes or SeHCAT test followed by prescription of bile acid binders within a period of 365 days, 3) Show differences in the frequency of BAD diagnosis in different regions of Denmark, 4) Provide information on the characteristics of individuals suffering from BAD, including lower education level, lower income, and higher number of contacts with health services compared to a comparable control group, 5) Track the use of liraglutide as a potential therapy for BAD. 1 …”
Section: Dear Editormentioning
confidence: 99%